A damage mechanics approach for lifetime estimation of wind turbine gearbox materials. (August 2020) - Jantara Junior, Valter Luiz; Basoalto, Hector; Papaelias, Mayorkinos
Highlights: Damage mechanics formulation based on a physics-based dislocation slip model. The formulation was implemented within a finite element scheme. Simulations carried out for a gear pair from a wind turbine gearbox. Simulation of severe service conditions, such as angular misalignment and lack of lubrication. Estimation for the remaining useful lifetime of these service conditions was generated. Abstract: Wind turbine gearboxes (WTG) have been suffering from premature failures and rarely live up to their designed lifetime. This study focuses on a better understanding of WTG failures. A finite element model of a gear pair was coupled with a constitutive model to quantify and predict damage, while also testing for different service conditions. A damage mechanics formulation is presented based on a physics-based dislocation slip model. Additionally, an estimation of the remaining useful lifetime of the component was generated, further assisting wind turbine farm operators to move towards the implementation of a truly predictive maintenance approach.